(untitled) (Global Journal of Management and Business Research, 2020)
Purpose: The article identifies the factors that delimit the concept of service quality in gyms sector. esign/methodology/approach: A systematic review was developed in which it adopted a reduced version of the protocol entitled Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The surveys were conducted in Emerald, Science Direct, and EBSCO databases; having as preliminary elegibility criteria the presence in the title, abstract or keywords of the following search terms: #x201C;service quality#x201D; or #x201C;fitness center#x201D;; #x201C;service quality#x201D; or #x201C;gym#x201D;; #x201C;service quality#x201D; or #x201C;health club#x201D;; #x201C;calidad del servicio#x201D; or #x201C;centro de fitness#x201D;. Twenty empirical articles were included, with the availability of the text in full, published in English, Spanish or Portuguese; and that effectively contributed to the purpose of the investigation